2013
DOI: 10.1016/j.bone.2013.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Lrp5 in osteocytes reduces Young's modulus and responsiveness to the mechanical loading

Abstract: Low-density-lipoprotein receptor-related protein 5 (Lrp5) is a co-receptor in Wnt signaling, which plays a critical role in development and maintenance of bone. Osteoporosis-pseudoglioma syndrome, for instance, arises from loss-of- function mutations in Lrp5, and global deletion of Lrp5 in mice results in significantly lower bone mineral density. Since osteocytes are proposed to act as a mechanosensor in bone, we addressed a question whether a conditional loss-of-function mutation of Lrp5 selective to osteocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 36 publications
1
50
0
Order By: Relevance
“…Conversely, skeletal unloading results in significant bone loss (12)(13)(14). Mechanical signals exert important influences on bone cells (12,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Osteocytes embedded in the bone matrix are thought to coordinate osteoblast and osteoclast activity in response to mechanical stimuli, translating mechanical strain into biochemical signals that ultimately regulate bone remodeling (i.e.…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, skeletal unloading results in significant bone loss (12)(13)(14). Mechanical signals exert important influences on bone cells (12,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Osteocytes embedded in the bone matrix are thought to coordinate osteoblast and osteoclast activity in response to mechanical stimuli, translating mechanical strain into biochemical signals that ultimately regulate bone remodeling (i.e.…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…bone resorption and formation) (9, 17-21, 25, 26). Accumulative evidence suggests that Wnt/␤-catenin signaling plays a critical role in mediation of the mechanical regulation of bone homeostasis (17)(18)(19)(20)(21)25). Osteocyte-derived sclerostin, which is encoded by the Sost gene (27), can be induced by mechanical unloading and inhibits Wnt/␤-catenin signaling in osteoblasts (12,28,29).…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…Homozygous deletion of either P2X7 or canonical Wnt signaling components in mice reduces anabolic responses of the skeleton to mechanical load [11,40,41]. The cross talk identified between these two pathways in the present study may help to explain how each increases osteoblast differentiation and bone formation during mechanotransduction.…”
Section: Physiological Roles Of P2x7-induced Potentiation Of Canonicamentioning
confidence: 58%
“…[12] These findings have been further confirmed by the demonstration that inactivation of LRP5 in osteocytes results in impaired bone size and mass in response to mechanical loading. [18] Although in the majority of cases of OPPG there is loss of function of the LRP5 gene, no mutation has been detected in a significant number of cases. Concepts have evolved and OPPG is now regarded as a member of an overlapping disorder, spondylo-ocular syndrome (SOS), which is also associated with eye abnormalities and vertebral compression fractures.…”
Section: The New Millenniummentioning
confidence: 99%
“…[20] More recently, Arantes et al [7] provided therapeutic insight into the management of OPPG and supported the rationale for using an osteoanabolic agent. Zhao et al [18] suggested that increasing LRP5-induced signalling in osteoblasts of persons with OPPG may be beneficial to the treatment of osteopaenia and osteoporosis.…”
Section: The New Millenniummentioning
confidence: 99%